Business model transformation toward sustainability: the impact of legitimation. Issue 8 (15th June 2020) - Biloslavo, Roberto; Bagnoli, Carlo; Massaro, Maurizio; Cosentino, Antonietta
Abstract : Purpose: This study aims to identify the legitimacy issues raised during a sustainable business model innovation, deployed by an Italian company, which was analyzed through the lens of the legitimation theory and the business model innovation theory. Design/methodology/approach: A single case study methodology is employed for empirical research. Semistructured interviews, with top and middle management, were conducted together with the analysis of several internal and external documents, to corroborate the case analysis. Findings: Results show how the potentiality of digital technologies allows the development of new sustainable business models, which, though, still need to gain legitimation to be accepted. The study findings allow drawing both on the business model innovation theory and on the legitimation theory, as they show how legitimation is a dynamic concept that involves internal as well as external stakeholders to support business model innovation. Originality/value: The paper is novel, since it addresses the topic of sustainable business models development, showing how companies can get legitimation. The paper builds on existing theories and provides a practical example.